2004
DOI: 10.1074/jbc.m409552200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in the Carboxyl Terminus of the Gap Junction Protein Connexin43 Indicates Signaling between Binding Domains for c-Src and Zonula Occludens-1

Abstract: Regulation of cell-cell communication by the gap junction protein connexin43 can be modulated by a variety of connexin-associating proteins. In particular, c-Src can disrupt the connexin43 (Cx43)-zonula occludens-1 (ZO-1) interaction, leading to down-regulation of gap junction intercellular communication. The binding sites for ZO-1 and c-Src correspond to widely separated Cx43 domains (ϳ100 residues apart); however, little is known about the structural modifications that may allow information to be transferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
223
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 183 publications
(242 citation statements)
references
References 78 publications
14
223
0
5
Order By: Relevance
“…This discrepancy is ascribable to differences in the experimental conditions: (i) the full length of the cytoplasmic C terminus was tested in that study (changes in conformation upstream to the PDZ binding domain could alter binding) (27), and (ii) in contrast with our studies, the C terminus was used as ligand. The shorter C-terminal Cx43 peptide (Cx43CT 20 ) used in our study competed against the interaction between (full length) Cx43CT and PDZ2 of ZO-1 in NMR studies (27), which is consistent with our observations. The ZO-1 PDZ domains we used for SPR analysis were human sequences, and the domain structure of human and teleost ZO-1 are very similar (37).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This discrepancy is ascribable to differences in the experimental conditions: (i) the full length of the cytoplasmic C terminus was tested in that study (changes in conformation upstream to the PDZ binding domain could alter binding) (27), and (ii) in contrast with our studies, the C terminus was used as ligand. The shorter C-terminal Cx43 peptide (Cx43CT 20 ) used in our study competed against the interaction between (full length) Cx43CT and PDZ2 of ZO-1 in NMR studies (27), which is consistent with our observations. The ZO-1 PDZ domains we used for SPR analysis were human sequences, and the domain structure of human and teleost ZO-1 are very similar (37).…”
Section: Discussionmentioning
confidence: 48%
“…4E was neither concentration-dependent nor reproducible. The lack of interaction of Cx35CT 15 with the PDZ2 domain did not result from a lack of instrumental sensitivity, as a peptide corresponding to the last 20 aa of the Cx43 C terminus (Cx43CT 20 ; PSSRASSRASSRPRPDDLEI), which includes the reported PDZ2 binding motif (27,33), bound with higher affinity to the PDZ2 domain of ZO-1 in a concentrationdependent manner ( Fig. 4F; one run on a chip with two levels of ligand).…”
Section: Cx35mentioning
confidence: 99%
“…Similarly, our results with the p38 MAPK inhibitor SB202190 indicate that the MAPK pathway is responsible, in part, for the inhibitory effects of S. aureus on functional GJC in astrocytes. However, the participation of other kinases that have been shown to interact with Cx43, such as PKC (Martinez et al, 2002;Reynhout et al, 1992), casein kinase 1 (Cooper and Lampe, 2002), PKA (Burghardt et al, 1995;TenBroek et al, 2001), and c-Src Sorgen et al, 2004) cannot be excluded in modulating the S. aureus-induced decrease in Cx43 expression, and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Yet recent studies have demonstrated that the interaction of Cx43 with ZO-1 appears to involve conserved residues in Cx43 that are upstream of the canonical C-terminal PDZ binding motif (Fanning et al 2007;Sorgen et al 2004), and further indicate that Cx43 C-termini might interface with ZO-1 homodimerized by PDZ2 interactions (Fanning et al 2007). Thus it remains possible that abrogation of PDZ-mediated Cx43-ZO-1 interaction by Cterminal tagging of Cx43 is due not only to masking of the terminal isoleucine residue (Giepmans and Moolenaar 1998), but also results from disruption of critical residues further upstream (and/or loss of ZO-1 dimerization).…”
Section: Resultsmentioning
confidence: 99%
“…ZO-1 has been shown to interact with several connexins, but the best characterized is Cx43 (Giepmans 2004). The second PDS95/dlg/ZO-1 (PDZ2) domain of ZO-1 is known to interact with the cytoplasmic C-terminal residues of Cx43 (Giepmans and Moolenaar 1998;Sorgen et al 2004). However, the physiological significance of direct PDZ2-mediated interaction between ZO-1 and Cx43 has remained elusive.…”
Section: Introductionmentioning
confidence: 99%